Sensor-controlled intelligent vehicle systems: demand and needs for a global automotive landscape - Hossain, Altab; Rahman, Mohammed Ataur (Elsevier, Ltd, 2014)
The main philosophies behind the research functions are the extension of knowledge, the solution of problems, evaluation of the truth, exploration, clarification and classification, and the establishment of correlation, among others. In particular, on vehicle dynamics, the automotive industry is compelled to reinvent itself in order to meet the challenges of a dramatically changing global automotive landscape with a wide variety of research tasks. Consequently, long-standing studies on vehicle dynamics, fuel efficiency,and consumer and governmental demands are playing important roles for research innovation, to a greater degree than ever before. In addition, in the emerging area of intelligent vehicle and highway systems (IVHSs), research philosophy has been implanted, notably from the exciting new developments on the horizon. The real necessity of developing an intelligent transportation system (ITS) in the automotive industry, especially in off-road transportation systems, has been explored deeply in academic and industrial research investigations. However, with growing environmental awareness, increasing demand for cross-country mobility, and human endeavors in agricultural fields, this research trend is also becoming increasingly important in the global automotive industry in regard to specialized off-road vehicles. Furthermore, transportation is an important problem for off-road vehicles in agriculture over swampy peat terrain, and it is considered one of the biggest issues in the many parts of the world. Subsequently, it has been found that the agricultural mechanization of swamp peat terrain transportation has been mainly restricted by the terrain’s low trafficability and high water table.The intelligent air-cushioned tracked vehicle (IACTV) has become one of the most viable alternatives to conventional vehicles such as fully tracked vehicles and fully wheeled vehicles in swamp peat terrain transportation due to its high floatation capacity, reduced power consumption (PC), and greater mobility. Therefore, in order to get reasonably good performance on low-bearing-capacity swamp peat terrain, a sensor-controlled intelligent system is considered to operate the air-cushioned system smoothly at any instant while on the terrain.